Characterization of intense laser-produced fast electrons using hard x-rays via bremsstrahlung. (25th September 2015) - Sawada, H; Sentoku, Y; Bass, A; Griffin, B; Pandit, R; Beg, F; Chen, H; McLean, H; Link, A J; Patel, P K; Ping, Y
Abstract: Energy distribution of high-power, short-pulse laser produced fast electrons was experimentally and numerically studied using high-energy bremsstrahlung x-rays. The hard x-ray photons and escaping electrons from various metal foils, irradiated by the 50 TW Leopard laser at Nevada Terawatt Facility, were recorded with a differential filter stack spectrometer that is sensitive to photons produced by mainly 0.5–2 MeV electrons and an electron spectrometer measuring >2 MeV electrons. The experimental bremsstrahlung and the slope of the measured escaped electrons were compared with an analytic calculation using an input electron spectrum estimated with the ponderomotive scaling. The result shows that the electron spectrum entering a Cu foil could be continuous single slope with the slope temperature of ∼1.5 MeV in the detector range. The experiment and analytic calculation were then compared with a 2D particle-in-cell code, PICLS, including a newly developed radiation transport module. The simulation shows that a two-temperature electron distribution is generated at the laser interaction region, but only the hot component of the fast electrons flow into the target during the interaction because the low energy electron component is trapped by self-generated magnetic field in the preformed plasma. A significant amount of the photons less than 100 keV observed in the experiment could be attributed to the low energy electrons entering the foil a few picoseconds later after the gating field disappears.